Childhood acne in a boy with XYY syndrome. (6th January 2014) - Kasparis, Christos; Loffeld, Annette
Abstract : A 3-year-old boy was referred to the dermatology department with a 12-month history of facial erythema associated with a papular-pustular facial eruption consistent with childhood acne. He had been diagnosed with XYY syndrome identified during genetic analysis for cardiac anomalies at birth. XYY syndrome is an aneuploidy of the sex chromosomes which affects 1 in 1000 male births. It is often asymptomatic and identified incidentally following genetic analysis for other conditions. The syndrome can be associated with an increased risk of learning difficulties and delayed language skills. Early diagnosis could alert physicians to the possibility of subtle developmental and learning abnormalities and result in prompt management. Our case highlights the fact that the presence of childhood acne could aid in the early detection of XYY syndrome.